Determination of fine magnetic structure of magnetic multilayer with quasi antiferromagnetic layer by using polarized neutron reflectivity analysis - Yongshi Zhong; Yuichiro Kurokawa; Gen Nagashima; Shu Horiike; Takayasu Hanashima; Daniel Schönke; Pascal Krautscheid; Robert M. Reeve; Mathias Kläui; Hiromi Yuasa (AIP Advances, 2020)
We carried out polarized neutron reflectivity (PNR) analysis to determine the fine magnetic structure of magnetic multilayers with quasi-antiferromagnetic (quasi-AFM) layers realized by 90-deg coupling using two Co90Fe10 layers, and quantitatively evaluated the magnetization of quasi-AFM layers. Two types of samples with different buffer layers, Ru buffer and a NiFeCr buffer, were investigated and the average angles between the respective magnetization of the two Co90Fe10 layers were estimated to be +/− 39 degrees and +/− 53 degrees. In addition, less roughness was found in the NiFeCr buffer sample resulting stronger 90-deg coupling. A perfect quasi-AFM is expected to be realized by a flat interface of the magnetic multilayer.